Emerging Roles of Extracellular Vesicles in Pneumococcal Infections: Immunomodulators to Potential Novel Vaccine Candidates - Parveen, Saba; Subramanian, Karthik (Frontiers in Cellular and Infection Microbiology, 2022)
The Gram-positive bacterial pathogen, Streptococcus pneumoniae is a major global health threat that kills over one million people worldwide. Pneumococcus commonly colonizes the nasopharynx asymptomatically as a commensal, but is also capable of causing a wide range of life-threatening diseases such as pneumonia, meningitis and septicemia upon migration into the lower respiratory tract and spread to internal organs. Emergence of antibiotic resistant strains and non-vaccine serotypes has led to classification of pneumococcal bacteria as a priority pathogen by the World Health Organization that needs urgent research into bacterial pathogenesis and development of novel vaccine strategies. Extracellular vesicles are spherical membrane bound structures that are released by pathogen and host cells, and influence bacterial pathogenesis as well as the immune response. Recent studies have found that while bacterial vesicles shuttle virulence factors and toxins into host cells and regulate inflammatory response, vesicles derived from the infected host cells contain both bacterial and host proteins that are antigenic and immunomodulatory. Bacterial membrane vesicles have great potential to be developed as cell-free vaccine candidates in the future due to their immunogenicity and biostability. Host-derived vesicles isolated from patient biofluids such as blood and bronchoalveolar lavage could be used to identify potential diagnostic biomarkers as well as engineered to deliver desired payloads to specific target cells for immunotherapy. In this review, we summarize the recent developments on the role of extracellular vesicles in pneumococcal infections and future prospects in developing novel therapeutics and diagnostics for control of invasive pneumococcal diseases.